Combined effect of polyphosphate kinase and lon protease in Streptomyces coelicolor A3(2) antibiotic production - Genel, Nagihan; Tunca, Sedef (Springer Heidelberg, 2024)
The bacterial stringent response is a global regulatory process in which polyphosphate kinase (Ppk) and lon protease are important players. Previous studies have shown that overexpression of the lon gene and deletion of the ppk gene significantly increased actinorhodin production in Streptomyces coelicolor (SCO). In this study, a recombinant SCO Delta ppk-lon cell, expressing the extra lon gene in Delta ppk cells, was simulated using a modified in silico (computational) model, ecSco-GEM, and the negative effect of Ppk on actinorhodin production was confirmed. In addition, we identified key enzymes that play a positive role in actinorhodin production. Of these, NADH dehydrogenase/complex-I, beta-ketoacyl-[acyl-carrier-protein] synthase III, glycine cleavage system, and superoxide dismutase were identified as the most significant. By confirming these results with experiments, we have shown that GEMs can be a reliable starting point for in vitro (lab-based) studies of Streptomyces. .
Keywords: Streptomyces coelicolor A3(2); ATP-dependent lon protease; Enzymatically constrained model; Actinorhodin production; Ensemble modelling